Reconstruction of nasopharyngeal defect with submental flap during surgery for nasopharyngeal malignant tumors - Ma, Hongzhi; Fang, Jugao; Zhong, Qi; Hou, Lizhen; Feng, Ling; He, Shizhi; Wang, Ru; Yang, Yifan (Frontiers in Surgery, 2022)
Objective: To investigate the feasibility and effect of a pedicled submental flap in postoperative defect repair of nasopharyngeal malignant tumors. Methods: Eight cases (six women, two men; age, 29–63 years) of postoperative defects after resection of malignant nasopharyngeal tumors with a lesion stage of (r) T1~3N0~2M0 were retrospectively analyzed. Preoperative enhanced thin-slice computed tomography of the neck was performed to predict the submental flap reflux vein. The submental flap was prefabricated during the operation, and the nasopharyngeal mass was removed through the parapharyngeal space approach combined with nasal endoscopy/mandibular external rotation/maxillary overturning. The submental flap was elevated to the nasopharyngeal defect area through the parapharyngeal space for repair. Results: Intraoperative examination confirmed that among the eight submental flaps, three had venous drainage into the internal jugular vein and five had venous drainage into the external jugular vein; these findings were consistent with the preoperative computed tomography findings. The size of the submental flap was 8–10 × 5–6 cm. The repair range reached the eustachian orifice on the healthy side and extended to the posterior wall of the maxillary sinus on the affected side. The flap extended to the posterior upper part of the nasal septum at the top, to the oropharynx at the bottom, and to the bony surface of the skull base at the deep side. Primary healing after surgery was achieved, and no flap necrosis occurred. After 3 to 77 months of follow-up, one patient with recurrent nasopharyngeal carcinoma after radiotherapy developed cervical lymph node recurrence again, one patient with adenoid cystic carcinoma had lung metastasis, and the remaining six patients had no recurrence. Conclusions: The pedicled submental flap is used to repair postoperative defects in the nasopharyngeal region through the cervical parapharyngeal space. It is a simple and fast procedure with adequate tissue volumes. The flap can effectively protect important structures such as the internal carotid artery and reduce the risk of infection and bleeding from postoperative wound exposure.